Efektivitas Cognitive Behavior Therapy dengan Teknik Thought Stopping untuk Menurunkan Tingkat Kecemasan Narapidana Penyalahgunaan Narkoba di Lapas Klas IIB Lubuk Basung - Elpika Yenes; Yeni Karneli (JKI (Jurnal Konseling Indonesia), 2022)
Anxiety is the highest effect upon inmates of drug abuse. Individuals with anxiety disorders can display behavior such as unwarranted fear, panic and anxiety. Panic and anxiety can overcome by giving cognitive behavior therapy with thought stopping. The purpose of this study is (1) to describe the feelings of drug abuse before treatment (pre-test), (2) to describe the anxiety of drug abuse inmates after treatment (post-test), (3) to test the effectiveness of a cognitive behavior therapy with thought stopping to lower the level of drug abuse. The research method used was a quantitative study method with a pre-experiment type. The experimental design used was the one group pre-test post-test design. The study sample includes as many as 40 individuals who were convicted of drug abuse and 10 who were drug-abused as experiment groups. The withdrawal samples used are purposive sampling. Research instruments used by the Likert scale model, data analyzed using Wilcoxon Signed Rank Test with the help SPSS of version 26.00. Research indicates that (1) a description of the anxiety condition of drug abuse prior to treatment (pre-test) appears in medium category, (2) of the drug abuse anxiety conditions following treatment (post-test) is in low category, (3) the cognitive behavior therapy with thought stopping was effective lowers the anxiety level of drug abuse by inmates.